NUTRITIONAL CARE PRACTICES AMONG HEALTHCARE WORKERS AT TIEN GIANG MENTAL HOSPITAL, DONG THAP PROVINCE, VIETNAM, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge, attitudes, and practices of healthcare workers regarding nutritional care at Tien Giang Psychiatric Hospital in 2025 and to analyze associated factors.Method: A cross-sectional study was conducted among 100 healthcare workers directly involved in patient care. Data were collected using a structured questionnaire based on Circular 18/2020/TT-BYT. Statistical analysis was performed using SPSS 22.0 software.Results: 40% of healthcare workers had satisfactory knowledge; 85% had a positive attitude; and 62% had satisfactory practices. Related factors included age, educational level, years of service, and participation in training (p < 0.05).Conclusion: Healthcare workers demonstrated moderate knowledge and positive attitudes but limited practice in nutritional care. Strengthening training and standardizing nutritional care procedures are urgently needed.
Keywords: Nutritional care, healthcare workers, psychiatric hospital, knowledge - attitudes - practices.